2009
DOI: 10.1111/j.1574-6941.2009.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern extraction of structural responses of gut microbiota to rotavirus infection via multivariate statistical analysis of clone library data

Abstract: This study developed a new statistical strategy for analyzing clone library data to observe whether there is a defined pattern in structural responses of gut microbiota to environmental perturbations. A large clone library of genus Bacteroides was constructed with fecal samples for each subject in rotavirus-infected (Group R) and healthy children (Group H). In all, 665 clones of the 12 Group H subjects and 284 clones of the nine Group R subjects were sequenced and classified into 34 operational taxonomic units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…The increase in pH and decrease in DM in the lumen were likely the result of an acid-base and electrolyte disturbance and increased intestinal secretion in response to RV infection (Gennari and Weise, 2008). The infection also reduced gut microbial diversity and increased Bacteroides relative abundance, which is consistent with the greater abundance of Bacteroides fragilis reported in RV-infected children compared with healthy controls (Zhang et al, 2009). B. fragilis is a commensal gut bacteria but is also recognized as an opportunistic pathogen commonly associated with diarrheal disease and clinical infections (Kato et al, 1999).…”
Section: Discussionsupporting
confidence: 64%
“…The increase in pH and decrease in DM in the lumen were likely the result of an acid-base and electrolyte disturbance and increased intestinal secretion in response to RV infection (Gennari and Weise, 2008). The infection also reduced gut microbial diversity and increased Bacteroides relative abundance, which is consistent with the greater abundance of Bacteroides fragilis reported in RV-infected children compared with healthy controls (Zhang et al, 2009). B. fragilis is a commensal gut bacteria but is also recognized as an opportunistic pathogen commonly associated with diarrheal disease and clinical infections (Kato et al, 1999).…”
Section: Discussionsupporting
confidence: 64%
“…C Zhang et al Zhang et al, 2009). The application of PLS-DA to bar-coded pyrosequencing data was robust and also sensitive enough to identify specific members of gut microbiota with health-relevant responses to diet, genotype or health phenotypes, including both minor species (at 1-5%) and major species (410% of total gut populations).…”
Section: Diet May Override Genotypes In Msmentioning
confidence: 99%
“…Archaeal and bacterial amo A clusters were classified according to Nicol et al (2008) and Zhang et al (2009), respectively. See Figure 1 for soil names.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Jia and Conrad (2009) found that, after ammonium addition, the changes in nitrification activity were paralleled by changes in the abundances of AOB but not of AOA. Thus, the likely involvement of the AOA in the process (Caffrey et al, 2007; Zhang et al, 2009; Wessén et al, 2011; Yao et al, 2011) suggested that AOA, in conjunction with AOB, should be used as proxies to monitor nitrification. Accordingly, both AOA and AOB have been recently suggested as good indicators of soil quality (Wessén and Hallin, 2011).…”
Section: Introductionmentioning
confidence: 99%